AI-Driven Green Digital Marketing UMKM Serdang Bedagai untuk Keberlanjutan Ekonomi Lokal Berbasis Asta Cita - Yochi Elanda; Ratna Sari Dewi; Fhikry Ahmad Halomoan Siregar (Politeknik Ganesha Medan, 2026)
Artificial intelligence-based digital marketing transformation has become a strategic necessity for MSMEs in improving competitiveness, business sustainability, and marketing performance. However, the utilization of Artificial Intelligence and the implementation of Green Digital Marketing in MSMEs in Serdang Bedagai Regency are still not optimal. This study aims to analyze the influence of AI-Driven Digital Marketing and Green Digital Marketing on business sustainability and marketing performance of MSMEs, as well as to examine the mediating role of business sustainability. The study used a quantitative explanatory approach with a sample of 100 MSMEs selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares-Structural Equation Modeling using SmartPLS. The results showed that AI-Driven Digital Marketing had a positive and significant effect on business sustainability with a coefficient of 0.367 and on marketing performance with a coefficient of 0.380. Green Digital Marketing had a positive and significant effect on business sustainability with a coefficient of 0.325, but did not directly affect marketing performance with a coefficient of 0.028. Business sustainability had a positive and significant effect on marketing performance with a coefficient of 0.287. However, business sustainability was unable to mediate the effect of AI-Driven Digital Marketing or Green Digital Marketing on marketing performance. This finding implies that MSMEs need to prioritize the use of AI for personalization, customer analysis, and promotional efficiency, and integrate green marketing practices with concrete operational evidence. Future research is recommended to use a longitudinal design, cross-sector samples, and add variables such as digital literacy, innovation capability, and consumer environmental awareness.